FRI0034 Rage Activity Influences Co-Development of Joint and Vascular Disease in RA. (15th July 2016) - Yu, S.; Wong, C.-K.; Li, E.K.; Tam, L.-S.
Abstract : Background: RAGE is expressed by many cells in blood and joints of RA and interacts with a variety of pro-inflammatory ligands, especially HMGB1 that are enriched in inflamed joint. The RAGE-ligand interaction leads to a sustained inflammatory response. Soluble RAGE (sRAGE) lacks the transmembrane and cytoplasmic domain of the cell surface full-length RAGE (flRAGE) and function as a decoy for RAGE ligand. Relatively little is known about factors that regulate sRAGE levels in human subjects and whether circulating levels reflect tissue RAGE expression and activity is unclear. The relationship between the up-regulation of flRAGE/HMGB1 and the level of "protective" sRAGE levels in RA is of obvious clinical interest. Objectives: To elucidate the balance between the expression of flRAGE on peripheral blood monocyte and dendritic cell (DC), and the plasma concentration of sRAGE and HMGB1 in patients with active RA compare to controls; To ascertain whether flRAGE expression profiles, plasma sRAGE and HMGB1 level correlated with disease activity or inflammatory markers in RA patients. Methods: 40 consecutive patients attending the rheumatology clinic at Prince of Wales Hospital, who fulfilled the 2010 ACR/RULAR classification criteria with active RA (28 joint disease activity score 28–4 [CRP] (DAS28)>3.2) and 40 age- and sex-matched healthy volunteers were recruited for this cross-sectional study. The expression profile of cellular transmembrane RAGE on peripheral blood monocyte (ILT3 + CD123 – ), total DC (ILT3 + CD14 – CD16 – ), myeloid DC (ILT3 + CD14 – CD16 – CD123 – ) and plasmacytoid DC (ILT3 + CD14 – CD16 – CD123 + ), plasma levels of HMGB1 and soluble RAGE in all RA patients and healthy controls were measured at baseline using flow cytometry and ELISA. In RA patients, associations with disease activity and severity variables were analyzed by simple and multiple linear regressions. Results: Protein expression of flRAGE on peripheral blood monocytes (ILT3 + CD123 – ), total DCs (ILT3 + CD14 – CD16 – ) and myeloid DCs (ILT3 + CD14 – CD16 – CD123 – ) were significant increased in RA patients with active disese compared with control subjects (all p<0.01) (no enough cells for flRAGE detection on plasmacytoid ILT3 + CD14 – CD16 – CD123 + DCs). Also, the flRAGE was more common in patients with cardiac affection. There was no statistically significant difference of the plasma level of HMGB1 from active RA patients as compared healthy controls (p>0.05). The plasma sRAGE level was significantly lower in patients compared to healthy controls (p<0.001), which correlated negatively with serum levels of CRP, ESR, DAS28 and high-density lipoprotein (HDL) (all p<0.05). Linear regrssion analysis detected CRP as significant predictors for sRAGE level. Conclusions: Autoimmunity-mediated inflammation might induce aberrant expression and activation of flRAGE while decreasing the plasma level of sRAGE in RA patients, subsequently leading to the augmented inflammatory response. Moreover, membrance flRAGE and sRAGE were associated not just with RA inflammation and autoantibody protein, but also with classical vascular risk factors for end-organ damage. These data suggest that RAGE activity influences co-development of joint and vascular disease in RA patients. Disclosure of Interest: None declared